The impact of the war in Ukraine on the perinatal period: Perinatal mental health for refugee women (pmh-rw) protocol - Rodríguez-Muñoz, Maria F.; Chrzan-Dętkoś, Magdalena; Uka, Ana; García-López, Helena S.; Krupelnytska, Liudmyla; Morozova-Larina, Olha; Vavilova, Alona; Molotokas, Antonina; Murawska, Natalia; Le, Huynh-Nhu (Frontiers in Psychology, 2023)
Background The aim of the Perinatal Mental Health for Refugee Women (PMH-RW) Project is to investigate the impact of the war on perinatal mental health: anxiety, post-traumatic stress, depression, and birth trauma symptoms. It will also evaluate the factors that serve as protective elements for the development of these potential diagnoses (such as personality traits, social support, sociodemographic characteristics, and access to medical/mental health services). Method An international observational cohort study with baseline data is being assessed in Ukraine (for internal refugees) and several European Countries (for external refugees). The study includes as participants both pregnant women and those who have recently given birth (with babies up to 1 year old). The assessment includes measures on depression (EPDS), anxiety (GAD-7), experiences during birth (City Birth Questionnaire), post-traumatic stress symptoms [Impact of events scale—revised (PTSD-R)], Personality (10-Item Personality Inventory-TIPI), and a questionnaire for socio-demographic data which also such social support. Conclusion This study will provide needed information for determining the impact of the Ukrainian Crisis on perinatal mental health by studying potential risk and protective factors. The data collected will be used to inform policymakers with useful information that can be used in the development of plans to protect and promote the mental health of the perinatal refugees impacted by this event. Also, it is our hope that data collected from this study will serve to plant the seeds for further research regarding the impact of the crisis in Ukraine on the offspring and to analyze how these events are affecting further generations. Clinical Trial Registration ClinicalTrials.gov, Identifier: NCT05654987.